Indirect Control of Single-Phase Active Power Filters using Harmonic Control Arrays - (:unkn) unknown (IEEE, 2017)
The ever increase of nonlinear loads in electric distribution networks causes many problems due to the high level of harmonic currents. This paper proposes a new technique for controlling a single phase shunt active power filter based on a selective compensation using the newly developed technique of harmonic control arrays. Simulation results confirm the appropriate selective harmonic compensation performance under different operating conditions.
Keywords: Harmonic control arrays; single-phase active power filter; selective compensation; electric distribution network; DISTRIBUTION-SYSTEMS; COMPENSATION; SUPPRESSION